Genomic insights on cgMLST markers, drug resistance, and urease cluster of Proteus mirabilis strains - Shitao Lian; Yadong Liu; Songnian Hu; Chen Shen; Yinping Ma; Peng Yin; Zilong He (Microbiology Spectrum)
ABSTRACT Proteus mirabilis, a significant pathogenic bacterium within the Enterobacteriaceae family, is widely distributed across various natural environments. This study conducted a genomic comparison analysis of 1,267 strains of P. mirabilis using extensive genome data from public databases. The objective was to elucidate the pan-genomic structure of P. mirabilis, revealing the composition and distribution of core and accessory gene families among different strains. Additionally, an attempt was made to construct a core genome multilocus sequence typing scheme specific to this species in order to enhance the precision of describing genetic diversity and evolutionary relationships. Furthermore, the study delved into the mechanisms of resistance of P. mirabilis to carbapenems and quinolones. Our findings underscore significant challenges posed by P. mirabilis in terms of antibiotic resistance, with widespread resistance observed particularly against beta-lactams and an increasing trend in resistance to carbapenems and quinolones. These results highlight the severity of P. mirabilis as a pathogen and underscore its rapid evolution and adaptability in developing resistance. This study aims to deepen our understanding of the antibiotic resistance of P. mirabilis, providing important insights for the development of future antimicrobial drugs, promoting effective treatment and control of this pathogen, and mitigating its threat to human health.IMPORTANCEThe bacterium Proteus mirabilis is a common pathogenic bacterium that is known to cause a variety of human infections. The drug-resistant genes carried by P. mirabilis present a significant challenge to clinical treatment, particularly in regard to the organism’s notable resistance to commonly used beta-lactam and quinolone drugs. Furthermore, the prevalence of the urease gene cluster of P. mirabilis at the urease gene level may be associated with the formation of kidney stones. The objective of the study is to analyze the bacterium’s drug resistance, urease gene clusters, and gene distribution in genomes in order to facilitate the development of antimicrobial drugs and improve the treatment and control of P. mirabilis infections.